2015
DOI: 10.1039/c5ob01815c
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease stability of boron-modified nucleic acids: application to label-free mismatch detection

Abstract: 5'-End boronic acid-modified oligonucleotides were evaluated against various nucleases at single and double stranded levels. The results show that these modifications induce a high resistance to degradation by calf-spleen and snake venom phosphodiesterases. More importantly, this eventually led to the development of a new label-free enzyme-assisted fluorescence-based method for single mismatch detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(8 reference statements)
0
7
0
Order By: Relevance
“… 360 To fully exploit the biological potential of boron-based ssDNA and dsDNA, it appeared necessary to evaluate their respective resistance to nuclease degradation. 361 Single and double stranded DNA were tested against different 3′- and 5′-end exonucleases (Exo I, Exo III, SVPDE and CSPDE). The results obtained demonstrated a high resistance of borono-based ODN to nuclease degradation ( Table 36 ).…”
Section: Modified Internucleoside Linkagesmentioning
confidence: 99%
See 1 more Smart Citation
“… 360 To fully exploit the biological potential of boron-based ssDNA and dsDNA, it appeared necessary to evaluate their respective resistance to nuclease degradation. 361 Single and double stranded DNA were tested against different 3′- and 5′-end exonucleases (Exo I, Exo III, SVPDE and CSPDE). The results obtained demonstrated a high resistance of borono-based ODN to nuclease degradation ( Table 36 ).…”
Section: Modified Internucleoside Linkagesmentioning
confidence: 99%
“…These results eventually led to the development of a new label-free enzyme-assisted fluorescence-based method for single mismatch detection based on the addition of SYBR Green I. 361 This dye exhibits a large fluorescence enhancement upon binding to dsDNA. Indeed, with mismatched target strands being digested much more rapidly, addition of SYBR Green I after 30 min of incubation induced a 17-fold intensity enhancement in the presence of the wild-type complementary strand.…”
Section: Modified Internucleoside Linkagesmentioning
confidence: 99%
“…These modified sequences have notably been employed to engineer reversible boronate internucleosidic linkages with 3′-ribonucleotidic partners under enzyme-free and activator-free conditions. Recently, we evaluated 5′-ended boronic acid-modified oligonucleotides against various nucleases at the single and double stranded levels. Our results revealed that this modification was able to improve the stability of the modified probe but also protect its complementary strand from degradation . This unique property was eventually used to detect single point mutations assisted by snake venom phosphodiesterase.…”
mentioning
confidence: 84%
“…Our results revealed that this modification was able to improve the stability of the modified probe but also protect its complementary strand from degradation. 38 This unique property was eventually used to detect single point mutations assisted by snake venom phosphodiesterase. In continuation to our work, we became interested in ribonuclease H (RNase H).…”
mentioning
confidence: 99%
“…To fully exploit the potential of boron‐modified oligonucleotides, we also investigated the resistance of 5′‐boronic acid modified sequences toward nucleases degradation both at the single and double stranded levels [67,68] . Among the many nucleases that were evaluated, snake venom phosphodiesterase (SVPD) and calf spleen phosphodiesterase (CSPD) provided the most interesting results.…”
Section: Biological Studies and Applicationsmentioning
confidence: 99%